Penataan dan Pembaharuan Kolam Hawai dalam Mewujudkan Desa Wisata Edukatif dan Dakwah Kultural di Desa Atue, Kecamatan Malili - Yusni Yusni; Ali Nahruddin Tanal; Dewi Furwana; Fadil Taufiq; Rostin Rostin; Muh. Alief Raihan; Rusni Rusni; Mutiah Nur Hikmah; Reskiani Reskiani; Siska Siska; Jumarni Jumarni; Misna Misna; Nahdatul Wahyu (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
This community engagement program aims to revitalize Kolam Hawai in Atue Village as an educational tourism space integrated with cultural da’wah values. The activity responds to the declining condition of the site, where most facilities were damaged and community participation in maintenance had decreased. The program employed the Asset-Based Community Development (ABCD) approach through five stages: discovery, dream, design, define, and reflect. Methods included observation, participatory interviews, focus group discussions, workshops, and collaborative action involving local youth, community leaders, women’s groups, and the Kolam Hawai management team. The findings show significant improvements in physical infrastructure, increased community involvement, and the emergence of new community structures managing the tourist site. The program also fostered behavioral changes toward environmental care and strengthened local leadership capable of sustaining future development initiatives. The revitalized Kolam Hawai now functions not only as a recreational space but also as a center for environmental education and cultural da’wah. These outcomes indicate that the ABCD approach is effective for strengthening local capacity and encouraging sustainable, community-driven social transformation.